Biogenic synthesis of silver nanoparticles using Rubus fruticosus extract and their antibacterial efficacy against Erwinia caratovora and Ralstonia solanacearum phytopathogens (vol 14, pg 5754, 2024) - Khan, Adnan; Ahmad, Nisar; Fazal, Hina; Ali, Mohammad; Akbar, Fazal; Khan, Ishaq; Tayyab, Mohammad; Uddin, Muhammad Nazir; Ahmad, Naveed; Abdel-Maksoud, Mostafa A.; Saleh, Ibrahim A.; Zomot, Naser; et al. (Royal Soc Chemistry, 2024)
Correction for 'Biogenic synthesis of silver nanoparticles using Rubus fruticosus extract and their antibacterial efficacy against Erwinia caratovora and Ralstonia solanacearum phytopathogens' by Adnan Khan et al., RSC Adv., 2024, 14, 5754-5763. https://doi.org/10.1039/D3RA06723H.